2022
DOI: 10.1007/s11356-022-24100-7
|View full text |Cite
|
Sign up to set email alerts
|

Sub-lethal doses of imidacloprid alter food selection in the invasive garden ant Lasius neglectus

Abstract: Despite several restrictions to their use, neonicotinoid insecticides are still widely employed worldwide. Residual sub-lethal amounts of these chemicals can have detrimental effects on the behavior of non-target insects. Toxic effects on economically important species such as bees have been widely documented, but less is known about their toxic action on other social insects, such as ants. In this study, we assessed the effect of different sub-lethal doses of the neonicotinoid imidacloprid on the ability of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 49 publications
(49 reference statements)
0
2
0
Order By: Relevance
“…Even though none of the chemicals tested showed an effect on learning and memory, we cannot exclude the possibility that these might interfere with foraging motivation through preference manipulation. Recently, sub-lethal doses of the neonicotinoid imidacloprid were shown to shift colony-level preference in the invasive ant Lasius neglectus ( Frizzi et al 2022 ). At the individual-level, orally administered serotonin decreases the amount of food ingested by treated ants ( Falibene et al 2012 ) whilst its antagonist, ketanserin, increases consumption ( Josens et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Even though none of the chemicals tested showed an effect on learning and memory, we cannot exclude the possibility that these might interfere with foraging motivation through preference manipulation. Recently, sub-lethal doses of the neonicotinoid imidacloprid were shown to shift colony-level preference in the invasive ant Lasius neglectus ( Frizzi et al 2022 ). At the individual-level, orally administered serotonin decreases the amount of food ingested by treated ants ( Falibene et al 2012 ) whilst its antagonist, ketanserin, increases consumption ( Josens et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, a recent study showed GABA promoting flower fidelity, suggesting its effects are complex (Calderai et al ., 2023). Interestingly, sub-lethal doses of the neonicotinoid imidacloprid, also an antagonist of nicotinic acetylcholine receptors, were shown to shift colony-level preference in the invasive ant Lasius neglectus towards toxicant-laced solutions (Frizzi et al ., 2022), even though imidacloprid has been shown to impair olfactory learning and memory in honeybees (Yang et al ., 2012; Williamson & Wright, 2013). However, were this the case, control attempts using spinosad as the toxicant would likely have been more successful, unless such effects are lost at high doses, as they are for caffeine and imidacloprid (Frizzi et al ., 2022; Galante et al ., 2024).…”
Section: Discussionmentioning
confidence: 99%